Virus-human chromatin interactions reorganise 3D genome and hijack KDM5B for promoting metastasis in nasopharyngeal carcinoma - Dittman Lai-Shun Chung; Zhaozheng Hou; Ying Wang; Kazi Anisha Islam; Songran Liu; Jiayan Liu; Larry Ka-Yue Chow; Yuki Yuk-Wun Wong; Cyrus Paak-Ting Chak; Yingpei Zhang; Lanqi Gong; Ziyang Qi; et al. (Nature Communications)
Abstract Epstein–Barr virus, the first identified human DNA tumour virus, is detectable in more than 90% of nasopharyngeal carcinoma patients in endemic regions. The 3D chromosome conformation analysis reveals that virus‒host chromatin interactions induce the spatial reorganisation of loops and compartments, resulting in “enhancer infestation” and switch of “H3K27 bivalency” at EBV-interacting regions. Through this mechanism, EBV hijacks KDM5B, a gatekeeper of genome stability, and its binding targets, leading to aberrant activation of an EBVIR-enhancer-KDM5B signature. Cancer cells with this signature present increased MYC activation, DNA damage responses, and epigenetic plasticity of epithelial-immune dual features with metastatic potential. Our multicentre multiomics study confirms that this signature is the prerequisite for chromosome instability and can be utilised as a risk factor for distant metastasis. This study highlights a mechanism in which latent viral episomes can alter the host high-order epigenotype, promoting transcriptional rewiring and metastasis in NPC.